The role of the tyrosine kinase Wzc (Sll0923) and the phosphatase Wzb (Slr0328) in the production of extracellular polymeric substances (EPS) by Synechocystis PCC 6803. Issue 6 (23rd January 2019) - Pereira, Sara B.; Santos, Marina; Leite, José P.; Flores, Carlos; Eisfeld, Carina; Büttel, Zsófia; Mota, Rita; Rossi, Federico; De Philippis, Roberto; Gales, Luís; Morais‐Cabral, João H.; Tamagnini, Paula
Abstract: Many cyanobacteria produce extracellular polymeric substances (EPS) mainly composed of heteropolysaccharides with unique characteristics that make them suitable for biotechnological applications. However, manipulation/optimization of EPS biosynthesis/characteristics is hindered by a poor understanding of the production pathways and the differences between bacterial species. In this work, genes putatively related to different pathways of cyanobacterial EPS polymerization, assembly, and export were targeted for deletion or truncation in the unicellular Synechocystis sp. PCC 6803. No evident phenotypic changes were observed for some mutants in genes occurring in multiple copies in Synechocystis genome, namely ∆ wzy (∆ sll0737 ), ∆ wzx (∆ sll5049 ), ∆ kpsM (∆ slr2107 ), and ∆ kpsM ∆ wzy (∆ slr2107 ∆ sll0737 ), strongly suggesting functional redundancy. In contrast, Δ wzc (Δ sll0923 ) and Δ wzb (Δ slr0328 ) influenced both the amount and composition of the EPS, establishing that Wzc participates in the production of capsular (CPS) and released (RPS) polysaccharides, and Wzb affects RPS production. The structure of Wzb was solved (2.28 Å), revealing structural differences relative to other phosphatases involved in EPS production and suggesting a different substrate recognition mechanism. In addition, Wzc showed the ATPase and autokinase activities typical of bacterial tyrosine kinases. Most importantly, Wzb was able to dephosphorylate Wzc in vitro, suggesting that tyrosine phosphorylation/dephosphorylation plays a role in cyanobacterial EPS production. Abstract : Many cyanobacteria produce extracellular polymeric substances (EPS) with unique characteristics that make them suitable for biotechnological/biomedical applications. However, these polymers are still underrepresented in the market and to optimize their production/characteristics, it is mandatory to understand their biosynthetic pathways. We demonstrated that two proteins—Wzc and Wzb—influence both the amount and composition of the EPS produced by the unicellular Synechocystis and provide insights into the molecular mechanism of cyanobacterial EPS production.